REBRANDING WEST JAVA: INTEGRATING VISIONARY LEADERSHIP, SOCIAL TRANSFORMATION, AND PLACE IDENTITY TO ACHIEVE COMPETITIVE ADVANTAGE AND INVESTMENT READINESS - Islami, Vina; Andriani, Ria; Harun, Muhamad; Heirunissa, Heirunissa (Dynamic Management Journal, 2025)
This study focuses on regional marketing strategies in West Java to address suboptimal economic development and to leverage local cultural potential in regional branding. The purpose of the research is to develop a conceptual model integrating visionary leadership, social transformation, and place identity to enhance investment readiness through the mediation of Sustainable Competitive Advantage (SCA), with environmental sustainability and infrastructure support as moderating variables. The method employed is qualitative conceptual analysis and a review of literature and reliable documentary sources. The findings produce a conceptual model showing that successful regional marketing strategies require a holistic synergy of leadership, Sundanese cultural values, and social innovation supported by sustainable practices. The study’s contribution and novelty lie in the multidimensional integration of regional branding strategies, focusing on SCA and investment readiness. The study’s limitation is its conceptual nature, necessitating empirical validation and gradual policy implementation.